The potential of soy pulp (Okara) as alternative protein source to tilapia fish (Oreochromis spp.) - Mohamad Basri, Mohd Noor (2015)
In the past years, fish meal was used as the main protein source in tilapia feed. However, due to the increase of price of the ingredients, a lot of research have been conducted to study the alternative protein source that can replace the fish meal. The feed costs can potentially be reduced by substituting the protein sources with lower cost ingredients. Given the relatively low price, soy pulp (Okara) may be a suitable alternative protein source in tilapia diet. Hence, this research were conducted to investigate the growth performance and feed utilization efficiency of tilapia, Oreochromis spp. fed with soy pulp (Okara) and fish meal pellet. For this purpose, 48 tilapia fingerlings were distributed into six experimental tanks comprises the two treatments with three replicates each for 28 days. The fish was fed twice daily and growth performance of the fish was analyzed weekly. Fishmeal pellet showed no significant difference (P>0.05) over soy pulp. The conclusion reached was that soy pulp could be used as an alternative feed for Oreochromis spp.